Feasibility of vessel wall imaging in assessing unruptured paraclinoid aneurysms: Clinical observations and preliminary experience. (March 2019) - Obusez, Emmanuel C.; Jones, Stephen E.; Mandell, Danny; Bullen, Jennifer; Gonzalez, Fernando; Hui, Ferdinand K.
Highlights: Traditional imaging DSA, MRA and CTA, are often equivocal and others may be inaccurate in determining the precise dural location of paraclinoid aneurysms. This study illustrates the possibility that vessel wall imaging may be a feasible tool in distinguishing the intradural or extradural location of paraclinoid aneurysms. Abstract: Introduction: The determination of the precise location of unruptured paraclinoid aneurysms with respect to the dura is essential in order to establish the risk of subarachnoid hemorrhage (SAH). In equivocal cases, current imaging modalities are often limited when trying to distinguish the precise relationship of these aneurysms with respect to the dura. We assessed the utility of vessel wall magnetic resonance (VW-MR) imaging in identifying the definitive location of unruptured paraclinoid aneurysms. Methods: We performed an observational retrospective review using a prospective database of patients undergoing 3T VW-MR of the brain. We included patients that underwent VW-MR gadolinium-enhanced T1-weighted black-blood sequences with fat suppression and saturation band to evaluate unruptured paraclinoid region aneurysms. The dural locations of the aneurysms were first identified on DSA or TOF-MRA and subsequently with VW-MR. The location of aneurysms on VW-MR were then compared qualitatively with the reference standard DSA/TOF-MRA by 2 neurovascular imaging experts. Results: Fifteen patients with unruptured paraclinoid region aneurysms were imaged with VW-MR. The extradural or intradural locations of the aneurysms were determined in 80% of patients using VW-MR compared to 47% with DSA/MRA. Conclusions: VW-MRI may be a feasible imaging technique for identifying the extradural or intradural location of unruptured paraclinoid aneurysms and may help guide management. Further larger studies may be warranted.